2012
DOI: 10.1155/2012/135132
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Properties of Nitrogen-Doped Bi12TiO20Synthesized by Urea Addition Sol-Gel Method

Abstract: Undoped and nitrogen-doped Bi12TiO20materials were synthesized by urea addition sol-gel method. By adding urea, undoped, and N-doped gel-type precursors were synthesized by low-temperature dehydrolyzation. Nitrogen-doped and undoped nanocrystalline Bi12TiO20were prepared by annealing at 600∘C for 30 minutes. From UV-Vis absorption and diffuse reflection spectrum, the absorbing band shifted from 420 to 500 nm by nitrogen doping. The bonds of Ti–N and N–O were identified by XPS spectra from the prepared material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Since the discovery of photoelectrochemical water splitting using TiO 2 electrodes [1], the investigation of the development of oxide semiconductor photocatalysts used for the degradation of environmental organic pollutants has attracted considerable attention for the past two decades [2][3][4][5][6][7][8]. Recently, Zn 2 SnO 4 is considered to be a promising photocatalyst due to its high electron mobility, high electrical conductivity, and favorable stability in acidic and basic solutions [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of photoelectrochemical water splitting using TiO 2 electrodes [1], the investigation of the development of oxide semiconductor photocatalysts used for the degradation of environmental organic pollutants has attracted considerable attention for the past two decades [2][3][4][5][6][7][8]. Recently, Zn 2 SnO 4 is considered to be a promising photocatalyst due to its high electron mobility, high electrical conductivity, and favorable stability in acidic and basic solutions [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was recognized that compared with metal doping (Ca 2+ , Sr 2+ , and Ba 2+ ) [6], transition metal ions (Fe 3+ , Cr 6+ , Co 3+ , and Mo 5+ [7][8][9][10]), rare earth cations (La 3+ , Ce 3+ , Er 3+ , Pr 3+ , Gd 3+ , Nd 3+ , and Sm 3+ ) [11], and some nonmetal doping (C [12], S [13], and F [14,15]), nitrogen-doped TiO 2 exhibited a valid process for narrowing the band gap and demonstrated a more appropriate solution for extending the photocatalytic activity of TiO 2 into the visible region [16][17][18][19][20][21][22]. Macak et al, and Shankar et al, and Allam and El-Sayed pointed out that the morphology, crystallinity, composition, and illumination geometry of nanotube arrays were critical factors in their performance as photoelectrodes [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors [ 30 , 31 , 32 , 33 , 34 , 35 ] reported a number of compounds based on the TiO 2 -Bi 2 O 3 system, which exhibit photocatalytic activity in the near-UV and visible range of the spectrum. Bismuth titanates of various compositions can be more effective as photocatalytic materials than that of TiO 2 because of their narrower band gap energy: TiO 2 -based photocatalysts are active only under UV irradiation with λ > 382 nm, while for bismuth titanate-based compounds, the activity can be achieved in the visible spectra range: for Bi 2 Ti 4 O 11 , λ > 400 nm, for Bi 12 TiO 20 , λ > 427 nm, for Bi 2 Ti 2 O 7 , λ > 496 nm, and for Bi 4 Ti 3 O 12 , λ > 421 nm.…”
Section: Introductionmentioning
confidence: 99%